First in vivo Evidence That Glutathione-S-Transferase Operates in Photo-Oxidative Stress in Cyanobacteria - Kammerscheit, Xavier; Chauvat, Franck; Cassier-Chauvat, Corinne (Frontiers in Microbiology, 2019)
Although glutathione (GSH) and GSH-dependent enzymes, such as glutathione transferases (GSTs), are thought to have been developed by cyanobacteria to cope with the reactive oxygen species (ROS) that they massively produced by their active photosynthesis, there had been no in vivo analysis of the role of GSTs in cyanobacteria so far. Consequently, we have analyzed two of the six GSTs of the model cyanobacterium Synechocystis PCC 6803, namely Sll1545 (to extend its in vitro study) and Slr0236 (because it is the best homolog to Sll1545). We report that Sll1545 is essential to cell growth in standard photo-autotrophic conditions, whereas Slr0236 is dispensable. Furthermore, both Sll1545 and Slr0236 operate in the protection against stresses triggered by high light, H2O2, menadione and methylene blue. The absence of Slr0236 and the depletion of Sll1545 decrease the tolerance to methylene blue in a cumulative way. Similarly, the combined absence of Slr0236 and depletion of Sll1545 decrease the resistance to high light. Attesting their sensitivity to high-light or methylene blue, these slr0236-sll1545 cells transiently accumulate ROS, and then reduced and oxidized glutathione in that order. In contrast, the absence of Slr0236 and the depletion of Sll1545 increase the tolerance to menadione in a cumulative way. This increased menadione resistance is due, at least in part, to the higher level of catalase and/or peroxidase activity of these mutants. Similarly, the increased H2O2 resistance of the slr0236-sll1545 cells is due, at least in part, to its higher level of peroxidase activity.